Promoter recognition by a complex of Spx and the C-terminal domain of the RNA polymerase alpha subunit. - Michiko M Nakano (PLoS ONE, 2010)
Spx, an ArsC (arsenate reductase) family member, is a global transcriptional regulator of the microbial stress response and is highly conserved amongst Gram-positive bacteria. Bacillus subtilis Spx protein exerts positive and negative control of transcription through its interaction with the C-terminal domain of the RNA polymerase (RNAP) alpha subunit (alphaCTD). Spx activates trxA (thioredoxin) and trxB (thioredoxin reductase) in response to thiol stress, and bears an N-terminal C10XXC13 redox disulfide center that is oxidized in active Spx.The structure of mutant Spx(C10S) showed a change in the conformation of helix alpha4. Amino acid substitutions R60E and K62E within and adjacent to helix alpha4 conferred defects in Spx-activated transcription but not Spx-dependent repression. Electrophoretic mobility-shift assays showed alphaCTD interaction with trxB promoter DNA, but addition of Spx generated a supershifted complex that was disrupted in the presence of reductant (DTT). Interaction of alphaCTD/Spx complex with promoter DNA required the cis-acting elements -45AGCA-42 and -34AGCG-31 of the trxB promoter. The Spx(G52R) mutant, defective in alphaCTD binding, did not interact with the alphaCTD-trxB complex. Spx(R60E) not only failed to complex with alphaCTD-trxB, but also disrupted alphaCTD-trxB DNA interaction.The results show that Spx and alphaCTD form a complex that recognizes the promoter DNA of an Spx-controlled gene. A conformational change during oxidation of Spx to the disulfide form likely alters the structure of Spx alpha helix alpha4, which contains residues that function in transcriptional activation and alphaCTD/Spx-promoter interaction. The results suggest that one of these residues, R60 of the alpha4 region of oxidized Spx, functions in alphaCTD/Spx-promoter contact but not in alphaCTD interaction.